Evaluating of DC-DC Buck-Boost Converter implementation for Integrated Solar Photovoltaic and Thermoelectric Cooler System - Priyo Adi Sesotyo; La Ode Muhamad Idris; Taufik Dwi Cahyono; Ery Sadewa (Sultan Publisher, 2025)
The growing demand for compact, efficient, and eco friendly cooling solutions has driven research into integrating thermoelectric coolers (TECs) with solar photovoltaic (PV) systems, where solar irradiance variability impacts cooling efficacy and energy efficiency. This challenge is addressed using DC-DC Buck-Boost converters whose performance is heavily influenced by control strategies such as Proportional Integral Derivative (PID) controllers employing tuning approaches that balance performance and prioritize disturbance rejection. This study investigates the implementation and performance of a DC-DC buck-boost converter in a solar photovoltaic and thermoelectric cooling (PV-TEC) system. Simulation-based analysis compared tuning methods for their ability to maintain thermal stability, reduce electrical input fluctuations, and enhance the TEC's Coefficient of Performance (COP). Results show that the PID controller significantly improves responsiveness and energy efficiency in dynamic solar conditions, achieving a 23% reduction in power consumption and a 36% increase in COP, highlighting the importance of adaptive control strategies.